Electrochemical determination of thiols: A perspective - White, P; Lawrence, N; Davis, J; Compton, R (2002)
Monitoring thiol concentrations within physiological fluids has risen to considerable importance within the biomedical communities as our appreciation of the various roles that these compounds can perform has increased. Their utilization as biomarkers for numerous clinical conditions has prompted considerable interest in the development of analytical protocols that enable speedy measurements to be made. As such, a large number of procedures have arisen. This perspective highlights the contexts where physiological thiol measurements are required and describes the basis of many of the current electrochemical approaches to their determination. The collation of information from a broad range of sources covering the major electrochemical approaches (direct, indirect, and post column/capillary detection) has been achieved and the salient points of each technique critically appraised. The various characteristics and limitations of the systems are compared and contrasted with the analytical parameters (matrix, methodology, detection limit etc) from each major grouping tabulated to aid direct comparison.